Migration, mobility, and modernization - Siddle, David (David J.) (Liverpool studies in European population, 2000)
This study gives fresh insights into the processes of movement of European populations, which reveal much more complex circulatory behaviour than the standard models derived from census and registration sources alone have suggested.